Impairment of the Body Image: Perceptions and Subjective Evaluations in Adolescents and Young Adults. Issue 7 (3rd October 2019) - Formica, Ivan; Pellerone, Monica; Iacolino, Calogero; Falduto, Maria Laura; Gualtieri, Stefania; Calabrese, Laura; Toscano, Carmela; Romeo, Elisa; Romeo, Gabriele; Romeo, Vincenzo Maria
Abstract : The construction of body image consists of the ways in which the body is considered, perceived, and evaluated. The ideal body image has been changing considerably over the centuries; the discrepancy between real and ideal body, today, leads many individuals to be dissatisfied with their body, develop negative feelings, and, in some cases, unhealthy behaviors. All this has led, in recent decades, to a sort of cult of the body. As a matter of fact, in Western culture the body has turned into an idol, a strict and demanding god to which one often becomes a slave. This article presents a bibliographical review on the main theories concerning body image, thus opening a space for reflection on its relative disorders, first of all that of body dysmorphism.